Draft Genome Sequence of Picalivirus D Recovered from San Francisco Wastewater - Greninger, Alexander L. (Genome Announc, 2015)
We report here the draft genome sequence of picalivirus D, a member of picalivirus, a picorna-like superfamily, and likely member of the order Picornavirales, assembled from metagenomic sequencing of organisms in San Francisco wastewater. This virus likely constitutes a novel genus within the picalivirus family.